PEMBERDAYAAN MASYARAKAT DESA POKAK KABUPATEN KLATEN DENGAN BATIK ECOPRINT - Y. Anni Aryani; Isna Putri Rahmawati; Evi Gantyowati; Doddy Setiawan; Taufiq Arifin (LPPM ITB AAS Indonesia Surakarta, 2022)
This activity was conducted in Pokak Village, Ceper District, Klaten Regency, Central Java. In this area, there are many leaves from trees, and it is a potential to develop for the empowerment of the Pokak village community. The people of the Pokak village can get additional income from the eco print batik industry, which can apply to fabric, leather, paper, and ceramic media. Ecoprint is a technique of giving a pattern to the media using natural materials. The results can be used as raw materials for clothing or other craft items such as umbrellas, fans, book covers, etc. The main problems are society does not have sufficient skills to manage leaves or tree waste (straw, onion peel, etc.), there are no tools used to support production, and human resources to be involved in empowerment activities. Service activities are carried out with training in making eco print batik on cloth media, both for pillowcases and batik cloth. In addition, this service activity provides equipment and supplies to support community empowerment in making eco print batik. Then, the service team also accompanied the recording of assets in the KSM. Keywords: eco print, batik, pokak